Object-Oriented Implementation of the Finite-Difference Time-Domain Method in Parallel Computing Environment - Chun, Kyungwon; Kim, Huioon; Hong, Hyunpyo; Chung, Youngjoo (Future Application and Middleware Technology on e-Science, 2009)
GMES which stands for GIST Maxwell’s Equations Solver is a Python package for a Finite-Difference Time-Domain (FDTD) simulation. The FDTD method widely used for electromagnetic simulations is an algorithm to solve the Maxwell’s equations. GMES follows Object-Oriented Programming (OOP) paradigm for the good maintainability and usability. With the several optimization techniques along with parallel computing environment, we could make the fast and interactive implementation. Execution speed has been tested in a single host and Beowulf class cluster. GMES is open source and available on the web (http://www.sf.net/projects/gmes).